Disponibilidade hídrica e hidrorretentores na produção de mudas clonais de eucalipto - Ramos, Klédison Alan (2012)
This study aimed to evaluate the use of two types of water retentor polymer, mixed with substrates in concentrations of 0,33, 0,66 and 1,00 Kg.m-³, submitted to three irrigation level: operational blade, blade 30% of reduction and blade 50% reduction in production of clonal eucalyptus seedlings (hybrid of E. grandis x E. urophylla) in nurseries, in two separate experiments to contribute to greater water retention, decreasing irrigation and maintaining quality of produced seedlings. The study was done in units of Fibria Celulose in Aracruz, ES and Jacarei, SP. The variables were evaluated to assess the quality standard operating seedlings, among witch stand out the survival, rooting, seedling height, stem diameter, leaf water potential, quality standard changes and substrate moisture. This study was concluded that irrigation with 30% reduction can be used without compromising the quality of seedlings and other variables. The experiment was a 7 x 3 factorial arrangement in a completely randomized design with 5 replications